The Effect of Self Service Technology and Service Quality Toward Customer Satisfaction of Bank Nagari Syariah Batusangkar Branch - Putri, Tania Ananda; Shabri, Husni (Denisya Smart Consulting, 2024)
The purpose of this study was to analyze the effect of self service technology and service quality on customer satisfaction of Bank Nagari Syariah Batusangkar Branch. The research method uses a quantitative approach. The population of this study consisted of 970 people who used the M-Banking application with a sample of 91 people. The analysis technique uses multiple linear regression analysis. The results showed that the variables of self service technology and service quality simultaneously influenced customer satisfaction. Partially self service technology and service quality also affect customer satisfaction at Bank Nagari Syariah Batusangkar Branch which uses the M-Banking application. The results of this study will implement bank management to be able to improve service and quality in order to maintain customer satisfaction.